PERLINDUNGAN HUKUM KREDITUR ATAS DEBITUR WANPRESTASI BERUPA PENJUALAN OBYEK HAK TANGGUNGAN - Sugianto, Anthony Adiputra (Universitas Ekasakti, 2023)
Putusan Nomor 9/Pdt.G/2018/PN Wsb jo Putusan Nomor 508/Pdt.G/2018/ PT Smg jo Putusan Nomor 1924K/Pdt/2019 regarding the lawsuit against the law between Lailatin Afifah and the Director of PT. Surya Yudha Bank. Lailatin Afifah filed a lawsuit over the sale of the mortgage object which will be carried out by PT Bank Surya Yudha through a public auction because it is considered an act against the law. The sale of the mortgage object was carried out because Lailatin Afifah as the debtor did not pay installments to PT Bank Surya Yudha on the grounds that she was having difficulty developing her business. The research method in journal writing uses normative juridical research methods, namely examining existing cases and associated with applicable laws and regulations. The sale of mortgage objects through a public auction is not an illegal act because this is the right of PT Bank Surya Yudha as stipulated in Pasal 20 UU Hak Tanggungan.